"What say ye gout experts?" a content analysis of questions about gout posted on the social news website Reddit. Issue 1 (December 2017) - Derksen, Christina; Serlachius, Anna; Petrie, Keith; Dalbeth, Nicola
Abstract Background Social media is increasingly used by patients to source information for managing chronic disease. The aim of this study was to understand patient information needs about gout by a content analysis of questions posted on the social news website Reddit. Methods We analysed questions posted onto the 'Gout sufferers unite' subreddit site. Two reviewers coded questions into categories (inter-reviewer kappa 0.70), with discordant coding resolved by a third reviewer. Data were analysed by calculating the frequency of questions within the categories. Where relevant, categories were further separated into sub-categories to allow organisation and interpretation of the data. Results We analysed 359 questions in 287 posts by 213 individuals. A wide range of questions arose. The single most common category related to uncertainty of diagnosis (22.3% questions), with questions about disease management common. Information-seeking about medications was generally cautious, with questions about side-effects, risk of flares after starting urate-lowering therapy, and decision to start urate-lowering therapy. Community users experiencing flares posted questions about flare management, including medications, sometimes in real-time. Dietary management questions included the effectiveness of dietary changes as a management strategy, choice of alcoholic beverage, and weight loss strategies. Questions about serum urate levels were rare (2.8% questions). Conclusions Questions about gout posted on the subreddit site most often related to uncertainty about symptoms and disease management strategies, with infrequent questions about serum urate testing, results or targets. These findings may inform development of strategies to address the information needs of people with gout.